The Pedagogical Challenge of Digital Slang: Navigating the Evolution of Language in an Educational Context - Hryshchenko, Oleksandr; et al. (European Journal of Social Science Education and Research, 2026)
The quick expansion of information and communication technologies has deeply altered linguistic practices, escalating to new forms of linguistic practices. This shift has a sociolinguistic aspect as it gave growth to digitally mediated slang challenging traditional didactic contexts. This paper analyses digital slang as a socially entrenched communicative practice with inferences for pedagogy, language consciousness, and instructive policy. Concentrating on TikTok, the study discovers how digital media milieus contribute to the development, rotation, and standardisation of slang, and how these progressions interconnect with social identity, multimodality, and learning. Sociolinguistic and educational theories were used in the methodology. They included digital literacy, social constructivism, and communities of practice. A mixed qualitative methodology with the combination of discourse analysis with object-oriented analysis of digital content were as well used. The results demonstrated that TikTok meaningfully transforms the linguistic, semantic, and pragmatic features of contemporary digital slang. Communication progressively leaves the norms of a linear text, developing into multimodal setups that mix text, audio, video, memes, and ephemeral content. This forms hybrid lexicons with widespread abbreviations, acronyms, phonetic adaptations, and memetic elements. From a didactical point of view, digital slang arises as a cognitive and social source rather than a nonconformity from standards. Its barring hazards warning learners’ communicative competence and critical digital literacy. The investigation promotes to approach digital slang from a pedagogical perspective in order to provide inclusive, context-aware language instruction that brings into line with modern digital communication performs.